Resistance to antibiotics of Escherichia Coli, Enterobacter Gergoviae and Klebsiella Pneumoniae during urinary infections at CHUJRA Antananarivo, Madagascar - Andrianarivelo, Andry Maharo; Aimé Ratsimbazafy, Arthur Bien; Ravaoarisaina, Zakasoa Mbololona; Rafaramalala, Solofo Sarah; Razanadrakoto, Ianja Iorenantsoa; Rakotondraoelina, Lalaina Mamenosoa; Raharisoa, Annie Armandine; Rafalimanana, Christian; Rasamindrakotroka, Andry (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Infections of the urinary tract remain among the most common problems facing the clinician. This work aims to determine the antibiotic resistance of E. coli, E. gergoviae and K. pneumoniae during urinary tract infections in the Microbiology laboratory of the Joseph Ravoahangy Andrianavalona Antananarivo University Hospital Center to allow a better therapeutic approach. Material & Methods: We carried out a retrospective and descriptive study on all of the E. coli, E. gergoviae and K. pneumoniae strains isolated from the urine of patients who attended the laboratory of Microbiology on CHUJRA Antananarivo with a suspected UTI between January 2004 and december 2014. Susceptibility to antibiotics was assessed by the disc diffusion technique on Mueller–Hinton agar (MH) or MH + 5% sheep blood, as recommended by the Antibiogram Committee of the French Microbiology Society as the antibiotics tested. Results: E. coli, E. gergoviae and K. pneumoniae were isolated from 577 of the 5836 patients who submitted a urine sample (9.89%). Almost three quarters of isolates were E. coli (72.96%), E. gergoviae was found in 7.80% of cases and K. pneumoniae in 19.23% of cases.Ampicillin, amoxicillin + clavulanic acid, ticarcillin, first generation cephalosporins, second generation cephalosporins, cyclins, and cotrimoxazole represent a very high resistance level for E. coli, E. gergoviae and K. pneumoniae in the vast majority of cases. Since 2008, the presence of ESBL has been lower than in previous years (p=0.02). Antibiotics that remain effective in the majority of UTI cases are nitrofurans, colistin, imipenem, amikacin and Piperacillin / tazobactam. Conclusions: These results confirm the presence of multi- resistant strains as in hospitals and community settings and the associated resistance to the most accessible antibiotics inevitably limits the choice of antibiotic in the establishment of adequate treatment.